Organogénesis in vitro en Dalbergia retusa (Papilonaceae) - Valverde Cerdas, Lisette (2004)
Plants were obtained via organogenesis from hypocotyl explants of Dalbergia retusa from in vitro germinated seedlings. Adventitious bud induction was achieved on Murashige and Skoog medium containing five BA (benzyladenine) concentrations. The best BA concentration for budding induction and budding development was 8.8μM. Shoot rooting was obtained on half-strength modified MS basal medium, supplemented with 20g.l-1 of sucrose and five concentrations of indole-3-butyric acid (IBA). The highest number of shoot rooting was obtained with 19.7μM IBA but the highest average number of roots for plantlet was achieved with 24.6μM IBA. Plants were transferred to greenhouse conditions.